Citra Perempuan dan Ketidakadilan Gender dalam Novel Masih Adakah Surga Untukku? Karya Naya R dan Air Mata Pernikahan Karya Rahmi Novaliza - Gusni, Nenri; Morelent, Yetty; Syofiani, Syofiani (Dharmas Education Journal (DE_Journal), 2025)
This research aims to describe the image of women and the form of gender injustice contained in the novel Masih Abadak Surga Untukku? by Naya R and Tears of Marriage by Rahmi Novaliza. This research uses a qualitative approach with a descriptive method and the main theory used is the theory of Sugihastuti and Suharto (2016) about the image of women and Fakih (2020) about gender injustice. The data collection technique is done by intensive reading, recording, and classifying relevant quotes from both novels. The results of the research show that the image of women in both novels includes physical, psychological, and social images. The physical image is described through the description of the female figure's body related to beauty, softness, and weakness. The psychic image appears from the feelings, thoughts, and inner struggle of female characters. While the social image is seen through the role of women in the family and society. On the other hand, the form of gender injustice found in the novel Masih Abadak Surga Untukku? includes subordination and workload, while the form of gender injustice in Air Mata Pernikanan includes marginalization, subordination, stereotypes, violence, and workload. An intertextual comparison between the two novels shows that the Tears of Marriage are more complex in representing gender inequality and the suffering of women in social relations, while Is There Still Heaven For Me? more emphasis on inner upheaval and the position of women in the family. The conclusion of this research is that both novels reflect the social reality of gender inequality that still binds women, although with different intensity and form.